Assess the Effectiveness of Videoassisted Teaching Regarding Life Style Modification on Knowledge and Practice Amongpatients with PCOD at Srmgeneral Hospital, Kattankulathur - P., Dr. Abirami (International Journal of Innovative Research in Medical Science, 2017)
Women with polycystic ovarian syndrome have chronic anovulation and androgen excess not attributable to another cause. This condition occurs in approximately 4% of women. The main aim of the study is to assess the effectiveness of video assisted teaching regarding lifestyle modification on knowledge and practice among patients with PCOD at SRM General Hospital Kattankulathur. One group pretest post-test, experimental research design was adopted for the present study. The sample size was 50 and non-probability purposive sampling technique was used for selecting the samples. The tool used for the study comprises of 2 sections. Section a Demographic Data, Section B- Structured questionnaire developed by the investigator which includes 30 questions to assess the knowledge and practice on life style modification regarding PCOD. The study was conducted at SRM General Hospital, kancheepuram district the data was analyzed and interpreted based on the objectives using descriptive and inferential Statistics. The result revealed that with respect to knowledge the mean value 10.66 with SD 3.47of pre-test and the mean value of 20.700 with SD 3.1 5 of post-test projects ‗t‘ value as 35.69 which is Statistically significant at P = 0.001 level, with respect to practice the mean value 10.34 with SD 3.77 of pre-test and the mean value of 21.28 with SD 3.85 of post-test projects ‗t‘ value as 34.44 which is statistically significant at P=0.001 level. Pearson‘s correlation was r=0.6 which was statistically significant at P=0.001 for knowledge and practice on life style modification. Regarding the association ,there was a significant association found between the knowledge on life style modification among patients with PCOD after video assisted teaching and the demographic variables like Age, Educational status, Occupation, Area of residence and monthly income